Lifelong learning for tourism : concepts, policy and implementation - Airey, David; Cuffy, Violet V.; Papageorgiou, Georgios C. (Routledge, 2018)
Since the middle of the last century tourism has demonstrated almost continual growth, with international tourist arrivals now recorded in excess of one billion per annum. Given the global socio-economic significance of tourism, it is imperative to develop educational opportunities for those working in tourism-related industries. These opportunities should fulfil the changing needs of both industry, travellers, and the learners themselves. While the concept of lifelong learning in the tourism industry plays an important role, it has received little academic attention to date. This book provides a theoretical overview of lifelong learning for tourism, exploring its history, practice and conceptualization. It demonstrates the importance of lifelong learning for tourism from a variety of perspectives, drawing on educational, industry, policy and socio-economic insights. The book explores managerial and political implications, critical issues, best practice examples, and draws on a range of international case studies to demonstrate theory in practice. Finally, it offers a conceptual framework for future curriculum approaches. This book will be of interest to students, scholars and practitioners of tourism studies, hospitality, business and management, and international development. It will also appeal to those interested in adult education, vocational training, professional development and pedagogy.- Resumé vydavatel
Keywords: cestovní ruch; studium a výuka; celoživotní vzdělávání; tourism; study and teaching; permanent education; elektronické knihy; sborníky; electronic books; papers of several authors